PENINGKATAN MINAT BELAJAR SISWA MELALUI PENGGUNAAN VIRTUAL LAB PADA PEMBELAJARAN FISIKA MASA PANDEMI MATERI OPTIK DI KELAS XI MIPA 1 SMA NEGERI 1 PURI (BEST PRACTICE) - Abdul Kholiq (Discovery : Jurnal Ilmu Pengetahuan, 2021)
This research is an on-case study in the form of best practice which aims to determine the responses and learning outcomes of students in class XI MIPA 1 SMA Negeri 1 Puri Optical material through the use of a virtual lab. This research was carried out in class XI MIPA 1 SMA Negeri 1 Puri involving 32 students consisting of 11 male students and 21 female students, carried out in April 2021. The research stages were planning, implementation (treatment), and observation (observation). The virtual lab used utilizes learning media facilities at the Ministry of Education and Culture's learning house. The results showed that the learning process using a virtual optical material lab in class XI MIPA 1 SMA Negeri 1 Puri gave positive responses to learning. Meanwhile, learning using a virtual lab gives results on the completeness of learning outcomes in Physics of optical material in class XI MIPA 1 SMA Negeri 1 Puri. Complete learning outcomes are achieved with a percentage of 90.6%. Keywords: interest in learning, virtual lab, optics.